Magnetic anomalies along the traverse route from Syowa to Mizuho Stations, East Antarctica - Kazuo Shibuya; Katsutada Kaminuma; Akira Ikami; Kiyoshi Ito (National Institute of Polar Research, 1984)
The 21st Japanese Antarctic Research Expedition (JARE-21) made aeromagnetic surveys along the traverse route from Syowa to Mizuho Stations by using a proton precession magnetometer. Reductions of International Geomagnetic Reference Field and diurnal variations were applied to the observed total intensity data, and the geomagnetic anomaly profile along the route was obtained. The uncertainty in the anomaly profile is considered to be 20-30nT. There is a characteristic anomaly around S16-S30 which ranges from -250 to 350nT. There is also another anomaly from H260 to Z50,which ranges from -270 to 140nT. Both anomalies have the wave-length of 10-30km. The correspondence of the ground data by JARE-17 with the obtained anomaly profile is rather good. The comparison of the geomagnetic anomaly profile with the previously obtained free-air gravity anomaly profile was made.